SOCIOECONOMIC DETERMINANTS OF PRESCRIPTION ANTIBIOTIC AND MEDICINE USE AND ITS RELATIONSHIP WITH FAMILY MEDICINE - Abdullah Tirgil (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Improper use and over-consumption of antibiotics have direct implications on the health of individuals as well as indirect consequences impacting limited health care budgets of countries. There is scarce evidence on the determinants of medicine and antibiotic consumption for developing nations. We examine the relationship between family medicine and physician-prescribed antibiotic consumption over the years. We use nationally representative Turkey's Health Surveys for the years 2008 through 2012. We employ a multivariate regression analysis by implementing the Ordinary Least Squares method to understand the factors which determine prescribed antibiotic and medicine use. Findings indicate that antibiotic utilization trend declines in 2010 and continue falling in 2012 as well compared to 2008. We also find that visiting family medicine increases the probability of antibiotic utilization, which is inconsistent with the aim of the Health Transformation Program. However, the positive relationship between the family medicine visit and antibiotic use weakened over the years. Although Turkey took several measures and succeeded to reduce antibacterial resistance to some extent, antibiotics are still the most resorted drug type among therapeutic groups.